Teachers' Candidates’ Perceptions and Their Knowledge of 21st-Century Skills - Dewi Satria Ahmar; Muhammad Fath Azzajjad; Lilies Tangge; Mohammad Jamhari; Ratman; Afadil (EduLine: Journal of Education and Learning Innovation, 2023)
The purpose of this study was to analyze the perceptions of teachers' candidates’ facing 21st-century skills. This research is a survey research, survey research activities carried out on students of Universitas Sembilanbelas November Kolaka from the Chemistry Education S-1 in 3 different batches. Data collection and collection were carried out from January to June 2021. The instrument is in the form of student perceptions in the form of 12 statements and 10 questions. The number of respondents who filled out the questionnaire was 40 people. The data analysis process was carried out by measuring the percentage of each statement and question. obtained information on 4C (communication, collaboration, critical thinking, and creativity) still obtained weaknesses in the level of understanding of the Knowledge of creative and innovative thinking, namely 15 respondents (37.5%) and the concept of understanding the knowledge of the teacher's social competence, namely 14 respondents (35%). The results of the study are taken into consideration for the learning process in courses related to the knowledge base of becoming a teacher, which is important to be carried out contextually in the process of direct practice in a formal environment in a measurable and sustainable manner.